2021
DOI: 10.1080/17938120.2021.1898190
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic policies and the Iranian economy in the era of sanctions

Abstract: This paper examines the impact of macroeconomic policies on the Iranian economy. The study covers the time between 1978-2017. The results illustrate the role of the money supply and government spending in supporting growth, although contributing to inflationary pressures in the long run, attesting to supply-side constraints. In the short-run, policies have aimed to provide support to the economy in the face of continued fluctuations with the oil price and spillovers from the geopolitical tensions attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In parallel, industrialization decreases carbon dioxide emissions while increasing carbon emissions (Taghizadeh-Hesary et al, 2022; Zakari & Khan, 2022). Remittance is a crucial income source and helps the economy expand (Guha & others, 2013; Kandil & Mirzaie, 2021; Meyer & Shera, 2017; Pradhan et al, 2008: Pradhan et al, 2008). For financial development, transfer payments are vital, and the demand for financial services increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In parallel, industrialization decreases carbon dioxide emissions while increasing carbon emissions (Taghizadeh-Hesary et al, 2022; Zakari & Khan, 2022). Remittance is a crucial income source and helps the economy expand (Guha & others, 2013; Kandil & Mirzaie, 2021; Meyer & Shera, 2017; Pradhan et al, 2008: Pradhan et al, 2008). For financial development, transfer payments are vital, and the demand for financial services increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on Iran's inflation have found significant evidence for the importance of money supply, nominal exchange rate, nominal interest rate, import prices and output (e.g. Bahmani-Oskooee, 1995;Liu and Adedeji, 2000;Celasun and Goswami, 2002;Abassinejad and Tashkini, 2005;Bonato, 2008;Kandil and Mirzaie, 2017;Monfared and Akın, 2017;Kandil and Mirzaie, 2021). Other studies highlight the importance of fiscal deficit and institutional arrangements that adversely affect central bank's independence (e.g.…”
Section: Inflation In Iranmentioning
confidence: 99%
“…Alavirad and Athawale, 2005;Kia, 2006;Samimi and Jamshidbaygi, 2011;Naini and Naderian, 2019;Mazarei, 2020). The potential impact of sanctions on Iran's macroeconomic condition is also a unique factor (Kandil and Mirzaie, 2021); their effects on inflation are explored in several studies. For example, Pourshahabi and Dahmardeh (2014) examine the joint inflationary effects from sanctions and speculative currency attacks.…”
Section: Inflation In Iranmentioning
confidence: 99%